Virtual Reality Planning of Microvascular Decompression in Trigeminal Neuralgia: Technique and Clinical Outcome - Fabrig, Oliver Dietmar; Serra, Carlo; Kockro, Ralf Alfons (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background A neurovascular conflict (NVC) is considered the cause of trigeminal neuralgia (TN) in 75% of cases, and if so, a microvascular decompression (MVD) can lead to significant pain relief. A reliable preoperative detection of NVC is essential for clinical decision-making and surgical planning, making detailed neuroradiologic imaging an important component. We present our experiences and clinical outcomes with preoperative planning of the MVD procedure in a virtual reality (VR) environment, based on magnetic resonance imaging (MRI) including magnetic resonance angiography (MRA) and magnetic resonance venography (MRV) sequences.Methods We analyzed the data of 30 consecutive MVDs in patients treated for TN, in a retrospective single-surgeon (R.A. Kockro) study. Out of the 30 cases, 26 were included. Preoperatively, MRA/MRV and MRI series were fused and three dimensionally reconstructed in a VR environment. All critical structures such as the trigeminal nerve as well as the arteries and veins of the cerebellopontine angle, the brainstem, the neighboring cranial nerves, and the transverse and sigmoid sinus were segmented. The NVC was visualized and a simulation of a retrosigmoid approach, with varying trajectories, to the NVC was performed. The intraoperative findings were then compared with the data of the simulation. The clinical outcome was assessed by a detailed review of medical reports, and follow-up-interviews were conducted in all available patients (20/26).Results The VR planning was well integrated into the clinical workflow, and imaging processing time was 30 to 40 minutes. There was a sole arterial conflict in 13 patients, a venous conflict in 4 patients, and a combined arteriovenous conflict in 9 patients. The preoperative simulations provided a precise visualization of the anatomical relationships of the offending vessels and the trigeminal nerves as well as the surrounding structures. For each case, the approach along the most suitable surgical corridor was simulated and the exact steps of the decompression were planned. The NVC and the anatomy of the cerebellopontine angle as seen intraoperatively matched with the preoperative simulations in all cases and the MVC could be performed as planned. At follow-up, 92.3% (24/26) of patients were pain free and all the patients who completed the questionnaire would undergo the surgery again (20/20). The surgical complication rate was zero.Conclusion Current imaging technology allows detailed preoperative visualization of the pathoanatomical spatial relationships in cases of TN. 3D interactive VR technology allows establishing a clear dissection and decompression strategy, resulting in safe vascular microsurgery and excellent clinical results.
Keywords: Dextroscope; microvascular decompression; trigeminal neuralgia; virtual reality